2021
DOI: 10.1103/physrevlett.127.013603
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Interaction of Heralded X-Ray Photons with a Beam Splitter

Abstract: We report the experimental demonstration of efficient interaction of multi-kilo-electron-volt heralded x-ray photons with a beam splitter. The measured heralded photon rate at the outputs of the beam splitter is about 0.01 counts=s which is comparable to the rate in the absence of the beam splitter. We use this beam splitter together with photon number and photon energy resolving detectors to show directly that when a single x-ray photon interacts with a beam splitter it can only be detected at either of the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 1 , for a summary of experimental results on the behavior of photons with respect to the quantum foundation). Through extensive literature research we have obtained, however, a limited amount of treatises that lead to a breakdown of the above identity, most notably, the construct of a beam splitter: It splits the wave but not the particle 2 , 3 , leaving one of the two branched-out waves devoid of the particle. The object of study of this paper is whether this particle-less wave contains energy and any associated quantification thereof.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , for a summary of experimental results on the behavior of photons with respect to the quantum foundation). Through extensive literature research we have obtained, however, a limited amount of treatises that lead to a breakdown of the above identity, most notably, the construct of a beam splitter: It splits the wave but not the particle 2 , 3 , leaving one of the two branched-out waves devoid of the particle. The object of study of this paper is whether this particle-less wave contains energy and any associated quantification thereof.…”
Section: Introductionmentioning
confidence: 99%
“…The object of study of this paper is whether this particle-less wave contains energy and any associated quantification thereof. If yes 2 , then any interferometric setup for quantum communication must consider the energy losses due to the split waves, a phenomenon that research laboratories have well observed but have overall relegated to quantum entanglement 4 . Yet theoretical derivations in Ref.…”
Section: Introductionmentioning
confidence: 99%